PERENCANAAN UMUM PENANAMAN MODAL (RUPM) KOTA TANGERANG SELATAN - Abdul Hamid (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
This study aims to formulate and plan for capital investment policy and also to formulating investment improvement strategy in South Tangerang City. The method used Analitycal Hierarchy Process (AHP) and SWOT analysis. From the result indicate the direction of policy stakeholders' opinion: (1) Improvement of Investment Climate, (2) Encouraging Investment Distribution, (3) Focus on Food Development, Infrastructure and Energy, (4) Empowerment of Micro, Small, Medium, and Cooperative (MSME), (5) Provision of Facilities, Convenience, and / or the Investment Incentives, and (6) Investment Promotion. The prioritized sectors are trade, industry, hotel and restauran as first priority sector with eigenvalues vector ​​of 0.232, the second priority is health sector with eigenvalues ​​vector of .202, the third priority of education with the third largest eigen vector 0.199, the fourth priority sectors is agriculture, livestock and fisheries with eigenvalues ​​vector of 0.192 and the last priority is tourism sector with eigenvalues ​​vector only of 0.169.DOI: 10.15408/sjie.v3i1.2054